1998
DOI: 10.1074/jbc.273.46.30576
|View full text |Cite
|
Sign up to set email alerts
|

Differential Expression of Aggrecanase and Matrix Metalloproteinase Activity in Chondrocytes Isolated from Bovine and Porcine Articular Cartilage

Abstract: The release of aggrecan catabolites from cartilage is an early event in the pathogenesis of degenerative joint diseases. The enzymes involved in this process are unknown, controversial, and the subject of intense investigation. In this paper we have utilized a recombinant substrate containing the interglobular domain (IGD) of aggrecan to study specifically aggrecanase versus matrix metalloproteinase (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
56
0

Year Published

1999
1999
2007
2007

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 64 publications
(61 citation statements)
references
References 30 publications
5
56
0
Order By: Relevance
“…A soluble form of IGD-aggrecanase activity was previously reported in a matrix-free agarose culture system (18), and the current study suggests that this activity is attributable to ADAMTS-4. Immunodepletion experiments also suggested that ADAMTS-4 accounts for 75% of the aggrecanase activity in media from IL-1-treated bovine cartilage explants, while ADAMTS-5 accounted for only 15% (22).…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…A soluble form of IGD-aggrecanase activity was previously reported in a matrix-free agarose culture system (18), and the current study suggests that this activity is attributable to ADAMTS-4. Immunodepletion experiments also suggested that ADAMTS-4 accounts for 75% of the aggrecanase activity in media from IL-1-treated bovine cartilage explants, while ADAMTS-5 accounted for only 15% (22).…”
Section: Discussionmentioning
confidence: 68%
“…Chondrocytes were isolated from the metatarsophalangeal joints of 3-6-month-old pigs, using established procedures (18). Cells were filtered through a 40-m nitex filter and washed, and then cell numbers were established.…”
Section: Sds-page Andmentioning
confidence: 99%
See 1 more Smart Citation
“…It was also considered that secondary cleavage of MMP-generated aggrecan metabolites by aggrecanase could mask the detection of any such catabolites in culture media. To test whether such a cleavage could occur, MMP-1-generated metabolites initiating with FFGVG … were incubated with soluble aggrecanase generated in conditioned medium from IL-1-stimulated porcine chondrocytes as previously reported [27]. Western blot analyses of this conditioned medium with MAbs BC-14 and BC-3 showed the lack of endogenous aggrecan catabolites in this preparation ( Figure 2B, lanes 1 and 5).…”
Section: Proteoglycan Catabolism In 4-day Cultures Of Bovine and Porcmentioning
confidence: 71%
“…Immunoblotting of membranes and incubations with primary and secondary antibodies was performed as previously described [27] using monoclonal antibodies (MAbs) or polyclonal antiserum as follows : MAb BC-13 (1 : 250) and MAb BC-3 (1 : 2000 ; [11]) recognizing the aggrecanase generated C-and N-terminal IGD neoepitopes ...ITEGE and ARGSV … respectively ; polyclonal anti-DIPEN (1 : 250 ; [13,19]) and MAb BC-14 (1 : 1000 ; [11,28]) recognizing the MMP-generated C-and N-terminal IGD neoepitopes … DIPEN and FFGVG … respectively ; and MAb 2-B-6 (1 : 10 000) recognizing a chondroitinase-generated chondroitin-4-sulphate disaccharide epitope. All Western blots were scanned and differences in staining intensity of digitized bands were assessed using NIH Image (version 1.55) software.…”
Section: Sds/page and Western Blottingmentioning
confidence: 99%